Voice of People with Fragile X Syndrome and Their Families: Reports from a Survey on Treatment Priorities - Weber, Jayne Dixon; Smith, Elizabeth; Berry-Kravis, Elizabeth; Cadavid, Diego; Hessl, David; Erickson, Craig (Brain sciences, 2019)
To date, there has been limited research on the primary concerns and treatment priorities for individuals with fragile X syndrome (FXS) and their families. The National Fragile X Foundation in collaboration with clinical investigators from industry and academia constructed a survey to investigate the main symptoms, daily living challenges, family impact, and treatment priorities for individuals with FXS and their families, which was then distributed to a large mailing list. The survey included both structured questions focused on ranking difficulties as well as qualitative analysis of open-ended questions. It was completed by 467 participants, including 439 family members or caretakers (family members/caretakers) of someone with FXS, 20 professionals who work with a person with FXS, and 8 individuals with FXS. Respondents indicated three main general areas of concern: Anxiety, behavioral problems, and learning difficulties. Important differences were noted, based on the sex and age of the individual with FXS. The results highlight the top priorities for treatment development for family members/caretakers, as well as a small group of professionals, and an even smaller group of individuals with FXS, while demonstrating challenges with “voice of the patient” research in FXS.